Ubi societas, ibi jus: o processo natural de regulação proveniente das relações em sociedade - Marinho, Naiara Carneiro (2019)
The present work aims to understand the societal relations from a biological point of view. The human beings, since the beginning of humanity, form social relationships amongst themselves, creating communities with certain cultural and normative parameters. This natural social contract, where social behaviour was understood as a strategy for survival against different environmental conditions, is formed amongst men by specific relational processes. In this work, the cooperative processes will be discussed as a whole, analyzing if/how cooperation was an essential tool in man's natural ability to behave following normative rules through mechanisms that prevent non-cooperative individuals. Based on the conclusions drawn from this analysis, an observation of how legal science is indeed affected by these processes, in the concerns of natural law and human rights, will also be made.